2008
DOI: 10.1021/es8010749
|View full text |Cite
|
Sign up to set email alerts
|

Polybrominated Diphenyl Ethers in Peregrine Falcon (Falco peregrinus) Eggs from the Northeastern U.S.

Abstract: A total of 114 peregrine falcon eggs from nests in Connecticut, Massachusetts, Maine, New Hampshire, Rhode Island, and Vermont were analyzed for polybrominanted diphenyl ethers (PBDEs). Eggs were collected from 1996 to 2006, excluding 1997 and 1998. Total PBDE concentrations ranged from 74.5 to 6610 ng/g wet weight, with a median of 440. These levels were generally higher than those observed in European peregrine eggs, but comparable to those in North American seabird eggs. Congener patterns differed from such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
81
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 35 publications
13
81
1
Order By: Relevance
“…Regardless of these assertions, the comparison of the levels of the sum PBDEs in the SGH samples with those of peregrine falcon eggs which exhibit similar dietary preferences with the SGH was made. Generally, the observed levels for SGH in this study were comparable to those reported for peregrine falcons eggs in most European studies, Spain (160 -3600 ng g , lw) (Lindberg et al, 2004;Vorkamp et al, 2005;Chen et al, 2008;Johansson et al, 2009;Park et al, 2009;Guerra et al, 2012).…”
Section: Comparison With Other Similar Studiessupporting
confidence: 89%
“…Regardless of these assertions, the comparison of the levels of the sum PBDEs in the SGH samples with those of peregrine falcon eggs which exhibit similar dietary preferences with the SGH was made. Generally, the observed levels for SGH in this study were comparable to those reported for peregrine falcons eggs in most European studies, Spain (160 -3600 ng g , lw) (Lindberg et al, 2004;Vorkamp et al, 2005;Chen et al, 2008;Johansson et al, 2009;Park et al, 2009;Guerra et al, 2012).…”
Section: Comparison With Other Similar Studiessupporting
confidence: 89%
“…We conclude that PBDEs did not influence thyroid hormones in eagles at environmentally relevant concentrations but that P OHPBDEs might have. However, research on thyroid hormone disruption of populations of wild birds highly exposed to PBDEs, such as urban peregrine falcons (Falco peregrinus), is indicated [45].…”
Section: Contaminants and Thyroid Hormonesmentioning
confidence: 99%
“…Concentrations of PBDEs in swallows also were relatively lower than those reported in greater trophic-level birds from the northeastern United States and other industrialized countries (Chen et al 2008;Johansson 2009;). However, concentrations of PBDEs in swallows from El Paso were greater than those observed in aplomado falcon eggs from two regions in Mexico (Mora et al 2011).…”
Section: Discussionmentioning
confidence: 66%